Embedded memory design for multi-core and systems on chip - Mohammad, Baker (Analog Circuits and Signal Processing, 2014)
This book describes the various tradeoffs systems designers face when designing embedded memory.  Readers designing multi-core systems and systems on chip will benefit from the discussion of different topics from memory architecture, array organization, circuit design techniques and design for test.  The presentation enables a multi-disciplinary approach to chip design, which bridges the gap between the architecture level and circuit level, in order to address yield, reliability and power-related issues for embedded memory.  ·         Provides a comprehensive overview of embedded memory design and associated challenges and choices; ·         Explains tradeoffs and dependencies across different disciplines involved with multi-core and system on chip memory design; ·         Includes detailed discussion of memory hierarchy and its impact on energy and performance; ·         Uses real product examples to demonstrate embedded memory design flow from architecture, to circuit design, design for test and yield analysis.